Potential of Bottom Ash as sand replacement material to produce sand cement brick - Abdul Wahab, Anuar; Arshad, Mohd Fadzil; Ahmad, Zakiah; Mohd Ridzuan, Ahmad Ruslan; Wan Ibrahim, Mohd Haziman (International Journal of Integrated Engineering, 2018)
Bottom Ash is a by-product from coal electrical power plant. It was classified as scheduled waste. About 1000 tonnes/day of Bottom Ash was produced and create a logistic problem to dispose. Bottom Ash used as sand replacement material to produce sand cement brick grade C5 and C10. The effect of Bottom Ash to compressive strength and density of brick containing Bottom Ash compared containing river sand was identified and discuss in this paper. From results obtained is found that Bottom Ash is highly potential to be use as sand replacement material in a production of sand cement brick. Even though the compressive strength of sand cement containing Bottom Ash is lower than sand cement brick containing river sand, but the properties is still satisfied standard requirement as stated in British Standard BS3921.